The Effect of Business Strategy on Company Performance with Earnings Management as an Intervening Variable - Selfiyan Selfiyan (Komunitas Dosen Indonesia, 2025)
This research was conducted to analyze the effect of business strategy on firm performance with earnings management as an intervening variable. Business strategy is a tool used by firms to achieve competitive advantage. This research refers to the concept of Miles and Snow to determine business strategies with the prospector and defender dimensions as different extreme strategies. In this research, business strategy is measured using three proxies: employee per sales ratio (EMPSAL), capital expenditure per total asset ratio (), and dividend payout ratio (DPR). Earnings management is measured by calculating discretionary accruals using the modified Jones model approach. Firm performance is measured using the profitability ratio with the net profit margin indicator. The population in this research consists of manufacturing companies listed on the Indonesia Stock Exchange from 2022 to 2024. The data used are secondary data by determining the research sample using the purposive sampling method and obtained as 16 firms from 171 firms with a total of 48 samples. Companies with prospector and defender strategies in this research are grouped using cluster analysis. The intervening variable in this research was tested using path analysis aided by SPSS 24. The results showed that (1) business strategy had no significant effect on earnings management, (2) earnings management had no significant effect on firm performance, and (3) business strategy had a significant effect on firm performance.